Memory, truth and justice in Medieval philosophy: an overview of the most influential theories (Circe de clásicos y modernos, 2021)
This article presents some of the most influential philosophical insights on memory, truth and justice in the Christian Middle Ages. In all of them are present, in different proportion, the two mainstream traditions, Neoplatonism and Aristotelianism. St. Augustine, Avicenna and Thomas Aquinas incarnate perspectives increasingly deplatonized on memory. As for the concept of truth, both Augustine’s theocentric and Aquinas’s adequationist standards are expressions of a mainstream that declines in the XIVth century. Finally, while Augustine introduces critically Cicero’s definition of justice, rooted in the Greek-Roman theory of natural law, Aquinas coordinates systematically Christian theism, natural law and Aristotelian political naturalism.
Keywords: memory; truth; justice; Christianity; Neoplatonism; Aristotelianism